Gen-Z: Eksplorasi Identitas Budaya dan Tantangan Sosial Dalam Era Digital (International Forum of Researchers and Lecturers, 2024)
Generation Z, born between the mid-1990s to the early 2010s, grew in a rapidly evolving era of digital technology. Exploring cultural identity and facing social challenges is two important aspects of Gen-Z's life in this era. This article presents an in-depth analysis of the cultural identity of Generation Z and the social challenges it faces in the context of digitalization. By blending empirical research and literature review, this article explores various aspects of Gen-Z's life, including how technology shapes their cultural identity, the impact of social media on mental health, and social challenges such as online activism and the pressure of conformity. By understanding this dynamic, we can help shape more effective policies and strategies to support the positive development of Generation Z in the digital age.